The Yamanies Service to al- Haj between the 4 – up to 9 centuries A.H. (Journal of the College of Education for Women, 2019)
The Yemen Kings and gaverners allered notable services to the pilgrims, whowere in their way to perform the pilgrimage to Mecca. Among them Al-Hysen IbnSalama (dead 384, Aih). The governer of Al- Zeadiea state, who concern aboutpilgrimage route from its beginning at Hudrumot to its end at Mecca Al Makruma, thedistant was estimated by 60th days to pass the way he also eastablished asystem ofwater “artesian wells” as long as the pilgrimage way also setting up large Mosqesesand Marking out the way of the caravans of pilgrimage to save these caravans fromlossing the right way, he setting up under ground water chanal started from Arafat toholy Mecca in order to ensure water supplies for the erea. This project was verycostly.The leady (Alam) (dead 545 A.H) took in her account finding condition ofsafty and real protaction to pilgrimage caravans route. So Yemeni pilgrime felt safetyin their way holy God House.She eliminated all sort of taxes imposed on the pilgrims to Mecca. She wascelebrated among her people as the “pilgrim because she pilgrimed many times.King Al-Sualihi (dead 459 A.H) spread his power upon Mecca after aperiod ofdisorder and chaos. He established role of Justic and restored order he brought foodand lowerd its prices. He covered Kaaba whith white dress of silk.The King Al- Munsor Al-Rasouli (dead 647 A.H) forced his power uponMecca for seven years (639-646), treated the people of Mecca in general and thepilgrimes in- particular in way of Kindness and Justice that had never been in practicebefore his rule- he also imposed stability and order. While King Al-Muzufir startedhis rule with notable dead by rebuilding some part of the Holy Kaaba and redressing itwith new cover of silk, as well as he preformed the prophet Mimbar (pulpit). He andthe King Ismail Al-Ashraf made permanent Almses for the Al-Shraf honorabledecendants of Mohammed and the common people of Mecca. Many kings of BniRasoul established three schools and Rebat of sufism in Holy Mecca which servicedpeople of Mecca.